Squeezing the Pips: International Pressures on Managers' Affective Well-being and Performance - Hosie, Peter; Forster, N.; Sevastos, Peter (2005)
Implicit in the drive for international competitiveness is the recognition that high erforming managers are essential for organisations to achieve and sustain competitive advantage. A critique is undertaken of the global economic pressures impacting on Western managers' jobs. The emphasis was on investigating an aspect of human behaviour with the potential to enhance managerial performance. Despite mixed empirical evidence from decades of research, there is support in the literature for the notion the 'happy-productive worker thesis.' A study is presented to establish which indicators of Australian managers' affective well-being and intrinsic job satisfaction predict dimensions of their contextual and task performance. A contribution of this study was to provide qualified support for the 'happy-productive worker thesis' by linking these conceptual bases and theories to managers' affective well-being, intrinsic job satisfaction and performance.